A metal nanowire-based slit porous skin electrode and a method for manufacturing the same
Patent Information
- Application Number
- CN202511856721.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-10
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-12-10
AI Technical Summary
其核心矛盾在于:提升透气性往往需要引入孔隙结构,而这会缩小有效导电面积,进而限制界面阻抗的进一步降低
本发明公开了一种基于金属纳米线的狭缝多孔表皮电极,该电极从皮肤贴附侧由内向外依次包括纳米线导电层与多孔弹性支撑层:其中,导电层为呈密排状态且带有狭缝的金属纳米线网络,弹性支撑层具备微米级孔隙结构,金属纳米线还部分嵌入至弹性支撑层内部。该电极通过金属纳米线表面改性、界面自组装及聚合物多孔结构调控等关键步骤制备而成,实现了导电网络与支撑结构的一体化成型。该电极同时具备高导电性(方阻可达10.2Ω/sq)、高拉伸性(拉伸率200%–600%)与优异透气性(透气率400–600 g・m-2・24h-1),即便在人体运动过程中,也能稳定采集皮电、心电、肌电等生理信号,为可穿戴医疗诊断领域提供了坚实且可靠的器件支撑。
Smart Images

Figure CN121667710B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of flexible electronics and wearable device technology, specifically relating to a slit porous skin electrode based on metal nanowires and its preparation method. Background Technology
[0002] Skin electrodes are the core components for interaction between epidermal electronic devices and the human body. They must simultaneously meet three core requirements: low interfacial impedance, high tensile strength, and good breathability. Their performance directly determines the accuracy of physiological signal acquisition and the comfort of long-term wear.
[0003] Currently, common epidermal electrodes are mainly classified into three structural types: thin-film, fabric, and porous. Thin-film electrodes employ a full-coverage conductive layer design, which helps reduce interfacial impedance but hinders the penetration of sweat and moisture. Fabric and porous electrodes, while possessing excellent breathability, suffer from increased interfacial impedance due to the discontinuous distribution of conductive materials and loose contact with the skin. The core contradiction lies in the fact that improving breathability often requires introducing porous structures, which reduces the effective conductive area and thus limits further reduction in interfacial impedance.
[0004] Most existing porous electrodes employ a process of "first preparing a porous substrate, then coating a conductive layer." This approach has the following problems: the conductive layer is difficult to continuously spread on the porous substrate, is prone to breakage, and thus affects conductivity; if the amount of conductive material is increased to compensate for the discontinuity in conductivity, it will clog the pores, leading to a decrease in air permeability (typically below 400 g·m³). -2 ・24h -1 Furthermore, the multi-step preparation process is cumbersome and not conducive to large-scale production.
[0005] To address the aforementioned issues, this invention proposes a slit-porous epidermal electrode based on metal nanowires and its preparation method, aiming to synergistically optimize the electrode's interfacial impedance, tensile properties, and air permeability. Summary of the Invention
[0006] To overcome the shortcomings of existing technologies and address the deficiencies in interfacial impedance, tensile strength, and breathability of current skin electrodes, this invention proposes a slit-porous epidermal electrode based on metal nanowires. This electrode consists of a nanowire conductive layer and a porous elastic support layer, and is fabricated through key steps including metal nanowire surface modification, interfacial self-assembly, and polymer porous structure regulation. This electrode combines high conductivity, high tensile strength, and excellent breathability, enabling stable acquisition of physiological signals such as skin conductance, electrocardiogram (ECG), and electromyography (EMG) even during human movement, thus laying a reliable device foundation for the field of wearable medical diagnostics.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of the present invention provides a slit-porous epidermal electrode based on metal nanowires, the electrode comprising a nanowire conductive layer and a porous elastic support layer; the conductive layer is a densely packed metal nanowire network with slits; the elastic support layer has micron-scale pores; and the metal nanowires are partially embedded in the elastic support layer. The metal nanowires include at least one of silver nanowires, gold nanowires, or copper nanowires; the porous elastic support layer is made of an elastomeric polymer, specifically including at least one of thermoplastic polyurethane, styrene-ethylene / butene-styrene block copolymer (SEBS), polyether block amide, polyvinyl butyral, or hydrogenated styrene-butadiene-styrene block copolymer.
[0008] The second aspect of this invention also provides a method for preparing the slit-porous epidermal electrode based on metal nanowires as described in the first aspect (method one), the method comprising the following steps: S1: The surface of the metal nanowires is modified using a hydrophobic modifier, purified and dispersed in a mixed solvent of the first solvent and the second solvent, and then an elastomer polymer is added and dissolved to obtain a composite solution. S2: The composite solution is dropped onto the surface of still water to form a liquid film. The first solvent diffuses into the water, the metal nanowires migrate to the liquid-liquid interface, and the elastomer polymer undergoes pre-solidification. S3: Adding an aqueous surfactant solution initiates interfacial flow, driving the nanowires to accumulate and align tightly, forming a conductive layer with slits. S4: Water and the residual first solvent in the system permeate and exchange through a slit network to form a porous structure inside the polymer, thereby forming a porous elastic support layer. After the solvent has completely evaporated, the electrode is retrieved and dried to obtain the electrode.
[0009] This method constructs a dynamic three-phase self-assembly system, enabling hydrophobic nanowires to migrate directionally to the interface under solvent exchange. External field stimulation triggers interfacial microrheology, promoting nanowire network reorganization and densification. Simultaneously, the aqueous phase triggers polymer internal topological reconstruction through nanoslits, forming a three-dimensional interconnected porous structure while maintaining the integrity of the nanowire network. This method achieves integrated and simultaneous molding of the conductive network and the porous support structure.
[0010] The third aspect of this invention also provides another method (method two) for preparing the slit porous epidermal electrode based on metal nanowires described in the first aspect, the method comprising the following steps: S1: The surface of the metal nanowires was modified using a hydrophobic modifier, and after purification, the nanowires were dispersed in a polar solvent to obtain a modified nanowire dispersion. S2: The dispersion is added to the water surface, and the nanowires are made to form a densely packed conductive layer with slits at the gas-liquid interface through an interface-driven method, and then transferred to a rigid substrate. S3: A porous elastic support layer is directly constructed on the conductive layer using the static breathing diagram method or the phase separation method. S4: The electrode is obtained after curing.
[0011] This method first forms a structurally complete and ordered close-packed nanowire conductive layer through interfacial self-assembly, and then constructs a porous polymer layer on it in situ using a breath diagram or phase separation method. This method controls the structure and morphology of the conductive layer and the support layer step by step, fundamentally solving the problems of discontinuous conductive layer, easy breakage and pore blockage in traditional processes, and ensuring that the electrode has high conductivity, high tensile strength and high air permeability at the same time.
[0012] Preferably, in method one or method two, the hydrophobic modifier is selected from one or more of n-octadecyl mercaptan, n-hexadecyl mercaptan, or n-dodecyl mercaptan.
[0013] Preferably, in Method 1 or Method 2, the specific method for surface modification of metal nanowires using a hydrophobic modifier is as follows: dispersing the metal nanowires in an alcohol solvent to prepare a dispersion with a concentration of 5-10 mg / mL, then adding the hydrophobic modifier, and completing the hydrophobic modification by stirring.
[0014] More preferably, in method one or method two, the metal nanowire is a silver nanowire with a diameter of 90 nm and a length of 20–60 μm.
[0015] More preferably, in method one or method two, the molar ratio of the hydrophobic modifier to the metal nanowire is 0.4‰-2‰.
[0016] Preferably, in the mixed solvent of Method 1, the first solvent is one of N,N-dimethylacetamide, N-methylpyrrolidone, or N,N-dimethylformamide (DMF); the second solvent is one of toluene, xylene, or n-hexadecane; and the volume ratio of the first solvent to the second solvent is 1:1 to 10:1.
[0017] More preferably, the mixed solvent in Method 1 is composed of DMF and toluene in a volume ratio of 5-8:1.
[0018] Preferably, in Method 1, the concentration of the modified metal nanowires in the composite solution is 7-15 mg / mL, and the concentration of the elastomer polymer in the composite solution is 1-7 mg / mL.
[0019] Preferably, in method one, the surfactant is one or more of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, or nonylphenol polyoxyethylene ether.
[0020] Preferably, in method one, the volume ratio of the composite solution to the surfactant aqueous solution is 1-3 mL: 40-70 μL, and the concentration of the surfactant aqueous solution is 0.1-1 wt%.
[0021] Preferably, in method one or method two, the outer surface of the porous elastic support layer is subjected to plasma hydrophilic treatment, or coated with a hydrophilic polymer on one side, or deposited as an ultrathin hydrophilic film on one side by vapor deposition. Combined with the hydrophobic modification of the nanowire surface, the electrode forms a wetting asymmetry, with the contact angle between the outer support layer and water ≤10° and the contact angle between the inner conductive layer and water ≥110°, thereby achieving unidirectional perspiration function.
[0022] Preferably, in method two, the polar solvent includes at least one of ethanol, methanol, n-propanol, N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), and acetone.
[0023] Preferably, in method two, the interface driving method includes interface driving caused by a movable baffle compression method or surfactant-induced interface flow.
[0024] More preferably, in method two, the interface driving method is to use surfactant-induced interfacial flow; the volume ratio of the modified nanowire dispersion to the surfactant aqueous solution is 1-3 mL: 40-70 μL, and the concentration of the surfactant aqueous solution is 0.1-1 wt%.
[0025] Preferably, in Method 2, the static breathing diagram method in step S3 specifically involves: dissolving the elastomer polymer in an organic solvent to prepare a polymer solution, then dropping it onto a substrate carrying a nanowire conductive layer and leveling it, transferring it to a constant temperature and humidity environment, introducing water vapor to regulate the relative humidity of the environment, and using the template effect of the water droplets to induce the formation of a porous elastic support layer, which is then cured to obtain a slit porous skin electrode; the polymer material includes SEBS (styrene-ethylene / butene-styrene block copolymer).
[0026] More preferably, in method two, the concentration of the polymer solution is 30-50 wt%, and the organic solvent includes toluene.
[0027] More preferably, in method two, the temperature of the constant temperature and humidity environment is room temperature, the humidity (i.e., water vapor saturation) is 70%-90%, and the processing time under the constant temperature and humidity environment is 1-10 minutes.
[0028] Preferably, in method one or method two, a dotted conductive adhesive is sprayed onto the surface of the conductive layer to impart adhesion properties to the electrode.
[0029] The fourth aspect of the present invention also provides the application of the slit porous skin electrode based on metal nanowires described in the first aspect in flexible electronics and wearable devices.
[0030] The slit-porous epidermal electrode based on metal nanowires prepared in this invention has unidirectional perspiration function and a breathability of 400–600 g·m³. -2 24h -1 It also meets the requirements that the interface impedance is less than 10kΩ at a frequency of 1kHz, the elongation is between 200% and 600%, and the thickness is between 1 and 50μm.
[0031] Compared with the prior art, the beneficial effects of the present invention are: This invention discloses a slit-porous epidermal electrode based on metal nanowires. The electrode comprises, from the skin-attachment side, a conductive nanowire layer and a porous elastic support layer, arranged sequentially from the inside out. The conductive layer is a densely packed network of metal nanowires with slits, while the elastic support layer possesses a micron-scale pore structure. The metal nanowires are partially embedded within the elastic support layer. This electrode is fabricated through key steps including metal nanowire surface modification, interfacial self-assembly, and polymer porous structure regulation, achieving integrated molding of the conductive network and the support structure. The electrode simultaneously exhibits high conductivity (sheet resistance up to 10.2 Ω / sq), high tensile strength (stretch rate 200%–600%), and excellent breathability (breathability 400–600 g·m⁻²). -2 ・24h -1 Even during human movement, it can stably collect physiological signals such as skin conductance, electrocardiogram, and electromyography, providing solid and reliable device support for the field of wearable medical diagnostics.
[0032] Specifically, the present invention has the following advantages: (1) By modifying metal nanowires, self-assembling interfaces and regulating polymer structures, the conductive network and porous support layer are synergistically formed. The resulting electrode has high conductivity, high tensile strength and high air permeability, and is suitable for stable acquisition of physiological signals under exercise conditions. (2) The metal nanowires are partially embedded in the elastic support layer, and the hydrophobic modification enhances the interfacial compatibility, which significantly improves the bonding force between the nanowires and the polymer substrate, ensuring the stability of the electrical performance of the electrode under tensile conditions. (3) It has the synergistic effect of optional one-way sweating function and porous structure to effectively remove sweat, avoid skin infiltration and irritation, has good biocompatibility, and is suitable for long-term skin contact use. Attached Figure Description
[0033] Figure 1 This is a schematic diagram illustrating the formation process of the liquid film in the slit porous epidermal electrode prepared in Example 1. Figure 2This is a schematic diagram of the process for preparing a slit porous skin electrode based on metal nanowires in Example 1, and a structural diagram of the slit porous skin electrode. Figure 3 The image shows a scanning electron microscope (SEM) image of the slit porous epidermal electrode obtained in Example 1, which shows a close-packed nanowire network with slits and a micron-sized pore structure. Figure 4 Box plots showing the pore size distribution of the slit porous skin electrodes obtained in Examples 1 and 2 illustrate the effect of different solvent ratios on the pore size. Figure 5 The image shows a SEM image of the silver nanowire conductive layer obtained in Example 3, which reveals a close-packed nanowire network structure with slits. Figure 6 This is a schematic diagram of the step-by-step preparation process of the slit porous skin electrode in Example 3; Figure 7 This is a box plot of the pore size distribution of the slit porous skin electrode obtained under different water vapor saturation conditions in Example 4; Figure 8 This is a graph showing the water vapor transmission rate test results of the slit porous epidermal electrode in Example 5, including data from the electrodes of Examples 1-3 and the non-porous control electrode. Figure 9 This is a table showing the sheet resistance changes of the slit porous epidermal electrode in Example 6 before and after immersion in a saturated sodium chloride solution; Figure 10 The tensile performance test curves of the slit porous skin electrode in Example 7 are shown in parallel and perpendicular directions to the nanowire arrangement. Figure 11 The image shows the surface wettability characterization results of the slit porous epidermal electrode in Example 8. The left image shows the nanowire conductive layer (i.e., the skin-contact side), and the right image shows the outer side after plasma treatment. Figure 12 The impedance spectra of the slit porous epidermal electrode in Example 9 are compared with those of commercially available electrodes a and b. Figure 13 The results show the stability test results of EDA signal acquisition by the slit porous epidermal electrode in Example 10 under static and game-playing states. Detailed Implementation
[0034] The specific embodiments of the present invention will be further described below. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0035] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments are all available through conventional commercial channels.
[0036] This invention provides a slit-porous epidermal electrode based on metal nanowires. The electrode comprises a nanowire conductive layer and a porous elastic support layer. The conductive layer is a densely packed network of metal nanowires with slits. The elastic support layer has micron-level pores. The metal nanowires are partially embedded in the elastic support layer. The metal nanowires include at least one of silver nanowires, gold nanowires, or copper nanowires. The porous elastic support layer is made of at least one of thermoplastic polyurethane, styrene-ethylene / butene-styrene block copolymer, polyether block amide, polyvinyl butyral, or hydrogenated styrene-butadiene-styrene block copolymer.
[0037] This invention also provides two methods for preparing the above-mentioned slit-porous epidermal electrodes based on metal nanowires. Method one includes the following steps: S1: The surface of the metal nanowires is modified using a hydrophobic modifier, purified and dispersed in a mixed solvent of the first solvent and the second solvent, and then an elastomer polymer is added and dissolved to obtain a composite solution. S2: The composite solution is dropped onto the surface of still water to form a liquid film. The first solvent diffuses into the water, the metal nanowires migrate to the liquid-liquid interface, and the elastomer polymer undergoes pre-solidification. S3: Adding an aqueous surfactant solution initiates interfacial flow, driving the nanowires to accumulate and align tightly, forming a conductive layer with slits. S4: Water and the residual first solvent in the system permeate and exchange through a slit network to form a porous structure inside the polymer, thereby forming a porous elastic support layer. After the solvent has completely evaporated, the electrode is retrieved and dried to obtain the electrode.
[0038] Method 2 includes the following steps: S1: The surface of the metal nanowires was modified using a hydrophobic modifier, and after purification, the nanowires were dispersed in a polar solvent to obtain a modified nanowire dispersion. S2: The dispersion is added to the water surface, and the nanowires are made to form a densely packed conductive layer with slits at the gas-liquid interface through an interface-driven method, and then transferred to a rigid substrate. S3: A porous elastic support layer is directly constructed on the conductive layer using the static breathing diagram method or the phase separation method. S4: The electrode is obtained after curing.
[0039] The following detailed description, with reference to embodiments, of the slit porous skin electrode based on metal nanowires and its preparation method.
[0040] Example 1: This embodiment aims to demonstrate the complete process of electrode fabrication using Method 1, and to confirm its "close-packed nanowire network with slits" and "micron-scale pore" structure through SEM images. Specifically: First, silver nanowires with a diameter of 90 nm and a length of 20–60 μm were selected and dispersed in anhydrous ethanol to prepare a dispersion with a concentration of 8 mg / mL. Then, a 0.005 mol / L solution of n-octadecyl mercaptan-ethanol was added dropwise to the above solution at a molar ratio of 0.5‰ to n-octadecyl mercaptan. The mixture was magnetically stirred at 500 rpm for 20 minutes at 25 °C to complete the hydrophobic modification. The modified dispersion was centrifuged at 5000 rpm for 2 minutes, the supernatant was removed, the precipitate was collected and redispersed in a mixed solvent composed of DMF (N,N-dimethylformamide) and toluene (volume ratio 8:1). Subsequently, 6 mg of thermoplastic polyurethane (TPU) particles were added, and the mixture was stirred at room temperature for 30 minutes until completely dissolved to obtain 2 mL of a composite solution with a modified silver nanowire concentration of 10 mg / mL. Simultaneously, deionized water is injected into a circular container with a diameter of 15 cm as the lower phase, with a deionized water level of 2-3 cm. Using a pipette, 2 mL of the composite solution is added dropwise to the surface of the aqueous phase at a rate of 20 μL / s to form a uniform liquid film. Figure 1 (The liquid film formation process is demonstrated.) At this point, DMF diffuses into the water, silver nanowires migrate to the liquid-liquid interface, and TPU pre-solidifies. Subsequently, 50 μL of a 0.1 wt% nonylphenol polyoxyethylene ether aqueous solution is added to the system. This solution induces interfacial flow effects, driving the silver nanowires to accumulate and achieve close arrangement, thereby forming a densely packed conductive layer with a slit structure. Water molecules and the residual DMF in the system permeate and exchange through the slit network, promoting the formation of a porous structure inside the TPU matrix. After the solvent has completely evaporated, the product is collected and dried to finally obtain a slit porous skin electrode.
[0041] The complete preparation process of this embodiment is as follows: Figure 2 As shown. The obtained electrodes were characterized by scanning electron microscopy (SEM), and their SEM images ( Figure 3 The electrode clearly displays a densely packed silver nanowire network with slits and a polymer support layer structure with micron-sized pores, as well as the characteristic of nanowires partially embedded in the polymer support layer. The measured thickness of the electrode is (10±5) μm, which meets the requirements for ultrathin characteristics (<50 μm).
[0042] Example 2: This embodiment aims to demonstrate the effect of different solvent ratios on the film pore size in Method 1 and to provide a basis for controlling air permeability. The preparation method is basically the same as in Example 1, except that silver nanowires with a diameter of 90 nm and a length of 20–60 μm are selected and hydrophobically modified according to the steps in Example 1. The modified nanowires are redispersed in a mixed solvent composed of DMF and toluene (volume ratio of 5:1); then 6 mg of thermoplastic polyurethane (TPU) particles are added, and the mixture is stirred continuously at room temperature for 30 minutes until completely dissolved to obtain 2 mL of a composite solution with a modified silver nanowire concentration of 10 mg / mL.
[0043] The electrode pore size prepared in this embodiment (DMF:toluene = 5:1) is compared and analyzed with that in Example 1 (DMF:toluene = 8:1). Figure 4 The results show that the pore size of the elastic support layer formed under a DMF:toluene volume ratio of 5:1 is significantly larger than that formed under an 8:1 ratio. This directly proves that the size of the micron-sized pores in the elastic support layer can be effectively controlled by adjusting the solvent ratio.
[0044] Example 3: This embodiment aims to demonstrate the specific process of preparation method two and verify that this method can pre-construct a structurally complete, closely packed, and slit-containing conductive nanowire layer. First, silver nanowires are hydrophobically modified using n-octadecyl mercaptan (molar ratio 1‰) according to the method in Example 1. After purification, they are redispersed in anhydrous ethanol to obtain 2 mL of a modified silver nanowire dispersion with a concentration of 10 mg / mL. Then, under constant temperature and humidity conditions, deionized water is injected into a 15 cm circular container as the lower phase, with a deionized water height of 2-3 cm. The dispersion is then dropped onto the surface of the aqueous phase at a rate of 0.5 mL / min, allowing it to automatically spread and form a uniform nanowire film. A movable polytetrafluoroethylene baffle is then used for radial horizontal compression to maintain the surface pressure of the silver nanowires at 20 nN / m, or 50 μL of a 0.1 wt% nonylphenol polyoxyethylene ether aqueous solution is added dropwise to drive the formation of a closely packed and slit-containing conductive nanowire layer.
[0045] The obtained conductive layer was characterized by SEM. Figure 5 This confirms that a structurally complete, continuous, and slit-containing close-packed silver nanowire network has been formed.
[0046] Furthermore, the conductive layer was transferred to a 3cm × 3cm glass substrate, and a porous polymer support layer was directly constructed on the nanowire conductive layer using the static breath mapping method: SEBS (styrene-ethylene / butene-styrene block copolymer; CAS number: 66070-58-4) was dissolved in toluene to prepare a 40wt% solution. 200μL of this solution was dropped onto the nanowire conductive layer loaded on the substrate. After leveling, the sample was transferred to a constant temperature and humidity chamber (25℃), and water vapor was introduced to control the relative humidity (water vapor saturation) at 80% for two minutes. The template effect of the water droplets condensed was used to induce the formation of a micron-sized porous SEBS film with pore sizes of 5–30μm. After the treatment, the sample was quickly moved out of the constant temperature and humidity chamber, and the polymer solidified to obtain a slit-porous skin electrode. The step-by-step preparation process of this embodiment is as follows: Figure 6 As shown.
[0047] Example 4: This embodiment aims to demonstrate that Method 2 can precisely control the electrode pore size by adjusting the water vapor saturation and treatment time. First, an electrode precursor with a close-packed silver nanowire network (i.e., a close-packed nanowire conductive layer with slits) is prepared according to the method in Example 3. The conductive layer is then transferred to a 3cm × 3cm glass substrate, and a porous polymer support layer is directly constructed on the nanowire conductive layer using the static breath mapping method. The difference lies in: During the construction of the porous polymer support layer, the sample was placed in a closed vapor treatment device, and water vapor was introduced for two sets of control experiments: the first set had a fixed treatment time of 2 minutes, with water vapor saturation adjusted to 70%, 80%, and 90%; the second set had a fixed water vapor saturation of 70%, with treatment times adjusted to 1 minute, 2 minutes, and 3 minutes. After treatment, the sample was quickly moved out of the constant temperature and humidity chamber, where the polymer solidified to form a porous structure. Statistical analysis of the pore size of the sample was performed using an optical microscope, and the results are as follows: Figure 7 As shown, it is confirmed that the pore size can be precisely controlled in the range of 5–30 μm by adjusting the water vapor saturation and the treatment time, providing a methodological support for the precise control of the electrode structure.
[0048] Example 5: This embodiment aims to verify the high air permeability of the slit-porous epidermal electrode obtained by the present invention, and highlights the technical effect of the present invention by setting a non-porous electrode as a control. To verify the air permeability of the slit-porous epidermal electrode obtained by the present invention, water vapor transmission rate tests were conducted on each electrode sample. In the slit-porous epidermal electrode, the nanowire conductive layer is on the skin-attaching side (inner side), and the porous elastic support layer is on the outer side.
[0049] This embodiment tested a total of five groups of electrode samples, including: the electrode prepared in Example 1, the electrode prepared in Example 2, the electrode prepared in Example 3 under 80% water vapor saturation for 2 minutes, the non-porous, non-hydrophilized electrode (preparation steps were similar to Example 3, but a polymer support layer was constructed under normal humidity conditions), and the non-porous electrode after hydrophilic treatment. For the electrodes requiring hydrophilic treatment: the electrodes prepared in Example 1, Example 2, Example 3 under 80% water vapor saturation for 2 minutes, and the non-porous electrode after hydrophilic treatment, were first treated unilaterally for 100 seconds using a low-temperature radio frequency plasma treatment instrument (power 80 W, working gas O2, flow rate 15 sccm) before testing to reduce the contact angle between the outer support layer and water to below 10°. A clean, dry permeation cup was used; the permeation cup was a commercially available YM-11 type. Fill the chamber with anhydrous calcium chloride desiccant (3.00g). During filling, ensure the desiccant surface is horizontal and the distance between the upper surface of the desiccant and the lower surface of the electrode sample is controlled at 3-4mm. Place the electrode sample, cut to a diameter of 2cm, with the test surface facing upwards, flat at the mouth of the permeation cup. Assemble the gasket and pressure ring in sequence and tighten the nut. Use ethylene tape to seal the test assembly consisting of the cup body, rubber gasket, and pressure ring along the side of the permeation cup to ensure a leak-free seal. Quickly place the sealed test assembly horizontally in a constant temperature and humidity chamber. Set the chamber parameters to temperature 38±0.5℃, relative humidity 90±2%, and airflow velocity 0.3-0.5m / s. Remove the assembly after equilibration for 0.5 hours. Initial accurate weighing: Immediately cover the permeation cup with its matching lid and place the test assembly in a silica gel desiccator at approximately 20°C for 0.5 hours to equilibrate. Weigh each sample in the test assembly according to its sample number, ensuring a weighing accuracy of 0.001g. The weighing time for a single sample should not exceed 30 seconds. Remove the lid and quickly place the test assembly back into the drying oven for 1 hour of continuous testing. A second weighing is required, and the weighing order of the test assembly must be consistent between the two weighings. Calculate the 24-hour water vapor transmission rate of the electrode sample using the mass difference between the two weighings (each electrode sample should be tested three times, and the average value should be taken). Test results are as follows: Figure 8 As shown, the porous electrode prepared by this invention exhibits excellent air permeability. Specifically, the water vapor transmission rate of the electrode in Example 2 reaches as high as 558.24 g·m⁻². -2 24h -1 In Example 4, the electrode was 492.18 g·m³. -2 24h -1 In Example 1, the electrode was 424.85 g·m⁻¹. -2 24h -1 In contrast, the transmittance of the non-porous, non-hydrophilized electrode was only 90.68 g·m⁻¹. -2 24h -1The permeability of the non-porous electrode treated with plasma hydrophilicity only increased to 105.32 g·m⁻¹. -2 24h -1 The above data analysis shows that the permeability of the porous electrode of the present invention is 4-6 times that of the non-porous electrode. This significant performance improvement is directly attributed to the unique micron-scale porous structure in the electrode. In particular, the electrode of Example 2, due to its DMF to toluene volume ratio of 5:1, forms a larger-sized, more interconnected pore structure, thus achieving optimal permeability. This example, through the establishment of a reasonable control, strongly demonstrates that the electrode of the present invention possesses "high permeability (permeability rate 400–600 g·m³)". -2 24h -1 Furthermore, this property mainly stems from its porous structure, rather than simply from surface hydrophilic treatment.
[0050] Example 6: This embodiment aims to optimize electrode conductivity by immersion in a saturated sodium chloride solution and to verify its high conductivity and performance optimization effect through a before-and-after comparison. The electrode prepared in Example 1 was selected and cut into 1cm × 1cm samples. First, its initial sheet resistance was measured as a control and recorded as R0. Then, at 25°C, 36.0g of sodium chloride was dissolved in 100mL of deionized water to prepare a saturated solution; the sample was completely immersed in the solution, and the sheet resistance was measured every 30 seconds after removing it and drying the surface solution. The total immersion time was 2 minutes. The results are as follows: Figure 9 As shown, the sheet resistance of the electrode decreased significantly after immersion, and the sheet resistance R1 stabilized at a low value after 120 seconds. The calculated sheet resistance reduction rate [(R0-R1) / R0×100%)] exceeded 60%. This self-controlled before-and-after experiment clearly demonstrates that saturated sodium chloride immersion can effectively improve electrode conductivity, with a sheet resistance reaching 10.2 Ω / sq.
[0051] Example 7: This embodiment aims to verify the high tensile strength of the electrode and its electrical stability under tension. The electrode prepared in Example 1 was selected, and the alignment direction of the silver nanowires was observed using a scanning electron microscope. Five 2cm × 1cm samples were cut along both the parallel and perpendicular directions of the nanowire alignment. A universal testing machine equipped with gold-plated copper conductive clamps was used, with a tensile rate set to 5mm / min, and stress-strain curves and resistance changes were recorded simultaneously.
[0052] The test results are shown in Figure 10. The electrode exhibits high elongation in both the parallel and perpendicular directions, reaching 200%–600%. More importantly, under strains as high as 500% in the parallel direction, the electrode's resistance change rate remains below 30%. This data demonstrates that the electrode maintains stable electrical properties under tension, thus ensuring stable acquisition of physiological signals such as skin conductance, electrocardiogram, and electromyography during movement.
[0053] Example 8: This embodiment aims to verify that unidirectional perspiration function can be achieved by asymmetric wetting treatment of the electrode. A 2cm × 2cm electrode prepared in Example 1 was used. The elastic support layer (non-conductive film side) was degreased and wiped with anhydrous ethanol, and then dried in a 65℃ vacuum drying oven for 5 min. A low-temperature radio frequency plasma treatment instrument (power 80W, working gas O2, flow rate 15 sccm) was used to treat one side of the support layer for 100 s. The results were characterized using a contact angle meter (test solution: deionized water, droplet volume 2 μL). Figure 11 As shown, the contact angle between the conductive layer of the nanowire (i.e., the skin-contact side) and water is 114°±3° (hydrophobic). Figure 11 The left image shows that the outer side treated with plasma has a water contact angle of 8°±2° (superhydrophilic). Figure 11 The right figure shows the significant wetting gradient. This, combined with the inherent porous structure of the electrode, constitutes the mechanism for achieving unidirectional perspiration: sweat can be driven from the hydrophobic skin contact side to the superhydrophilic outer side and discharged, while preventing the backflow of external liquids.
[0054] Example 9: This embodiment uses electrochemical impedance spectroscopy to quantitatively evaluate the interfacial performance of the electrode of the present invention in practical applications. The slit-porous epidermal electrode prepared in Example 1 was selected as the experimental group, and two commercially available mainstream gel electrodes (labeled as commercial electrode a and commercial electrode b, respectively) were used as the control group. Electrode a is a commercially available dry electrode made of ABS plated with silver chloride; electrode b is a commercially available gel electrode made of non-woven fabric and conductive hydrogel. Both meet the technical requirements for therapeutic surface electrodes. Electrode a was purchased from Shenzhen Qiongshi Technology Co., Ltd., and electrode b was purchased from Guangzhou Daiguanjia Medical Device Co., Ltd. Five healthy adult volunteers (aged 22-30, male-to-female ratio 3:2) were invited to participate in the experiment. The experiment was conducted under standard environmental conditions (temperature 25±1℃, relative humidity 50±5%). All electrode samples were uniformly cut to 1 cm × 1 cm and attached to the same anatomical location on the inner forearm of the volunteers. Impedance spectroscopy measurements were performed, with a scanning frequency range of 0.1 Hz to 100 kHz, and a sinusoidal perturbation signal of 10 mV RMS was applied. The test examined two physiological states: a resting state (volunteers sat and rested for 15 minutes to ensure their skin was completely dry) and an exercise state (volunteers completed a standardized upper limb exercise program until their skin showed even, slight sweating).
[0055] Test results are as follows Figure 12As shown, at the characteristic frequency of 1 kHz, the interfacial impedance of the electrode of the present invention in a static state is (8.5±0.7) kΩ, significantly lower than that of commercially available electrode a (32.5±2.8) kΩ and electrode b (38.4±3.5) kΩ (p <0.01). Under conditions of slight sweating during exercise, the impedance of the electrode of the present invention only slightly increases to (9.4±0.8) kΩ, with the rate of change controlled within 10.6%; while the impedances of the two commercially available electrodes a and b jump to 58.6 kΩ (+80.3%) and 72.3 kΩ (+88.3%), respectively, showing serious performance degradation. In the full-band analysis, the electrode of the present invention maintains a smooth impedance attenuation curve from low frequency to high frequency, and the internal impedance value in the key frequency band of physiological signals of 10-1000 Hz remains stably below 50 kΩ.
[0056] Example 10: This embodiment verifies the signal fidelity, dynamic response capability, and biocompatibility of electrodes by collecting skin conductance (EDA) signals from the human body under multiple scenarios. Electrodes from Example 1, treated with hydrophilicity (see Example 5 for specific treatment methods), were attached to the inner forearm of healthy volunteers, and EDA signals were recorded using a biosignal acquisition system. The test lasted 400 seconds, during which volunteers sequentially experienced the preparation phase (resting), the game phase (emotional stress + light exercise), and the game end phase (resting) of a game (Switch game - Spraton 3). Figure 13 The test results showed that in the resting state (game preparation / end phase): the EDA signal baseline was stable; in the emotional stress + mild exercise phase: the signal response time was rapid, and the electrode could accurately capture the conductance peak; throughout the process, the volunteers experienced no skin discomfort, and the electrodes adhered firmly without falling off. This indicates that the electrode of the present invention exhibits high fidelity, fast response, and strong stability in EDA signal acquisition on the human body surface, and also has good biocompatibility.
[0057] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.
Claims
1. A slit-porous epidermal electrode based on metal nanowires, characterized in that, The electrode is composed of a nanowire conductive layer and a porous elastic support layer; the conductive layer is a densely packed network of metal nanowires with slits; the elastic support layer has micron-scale pores; and the metal nanowires are partially embedded in the elastic support layer. The metal nanowires include at least one of silver nanowires, gold nanowires, or copper nanowires; the porous elastic support layer is made of an elastomeric polymer, specifically including at least one of thermoplastic polyurethane, styrene-ethylene / butene-styrene block copolymer, polyether block amide, polyvinyl butyral, or hydrogenated styrene-butadiene-styrene block copolymer. The method for preparing the slit-porous epidermal electrode based on metal nanowires includes the following steps: S1: The surface of the metal nanowires is modified using a hydrophobic modifier, purified and dispersed in a mixed solvent of the first solvent and the second solvent, and then an elastomer polymer is added and dissolved to obtain a composite solution. S2: The composite solution is dropped onto the surface of still water to form a liquid film. The first solvent diffuses into the water, the metal nanowires migrate to the liquid-liquid interface, and the elastomer polymer undergoes pre-solidification. S3: Adding an aqueous surfactant solution initiates interfacial flow, driving the nanowires to accumulate and align tightly, forming a conductive layer with slits. S4: Water and the residual first solvent in the system permeate and exchange through a slit network to form a porous structure inside the polymer, thereby forming a porous elastic support layer. After the solvent has completely evaporated, the electrode is retrieved and dried to obtain the electrode.
2. The slit-porous epidermal electrode based on metal nanowires according to claim 1, characterized in that, The hydrophobic modifier is selected from one or more of n-octadecyl mercaptan, n-hexadecyl mercaptan, or n-dodecyl mercaptan.
3. The slit-porous epidermal electrode based on metal nanowires according to claim 1, characterized in that, The first solvent is one of N,N-dimethylacetamide, N-methylpyrrolidone, or N,N-dimethylformamide; the second solvent is one of toluene, xylene, or n-hexadecane; the volume ratio of the first solvent to the second solvent is 1:1 to 10:
1.
4. The slit-porous epidermal electrode based on metal nanowires according to claim 1, characterized in that, The surfactant is one or more of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, or nonylphenol polyoxyethylene ether.
5. The slit-porous epidermal electrode based on metal nanowires according to claim 1, characterized in that, The outer surface of the porous elastic support layer is treated with plasma hydrophilicity, or coated with a hydrophilic polymer on one side, or deposited with an ultrathin hydrophilic film on one side by vapor deposition.
6. A slit-porous epidermal electrode based on metal nanowires, characterized in that, The electrode is composed of a nanowire conductive layer and a porous elastic support layer; the conductive layer is a densely packed network of metal nanowires with slits; the elastic support layer has micron-scale pores; and the metal nanowires are partially embedded in the elastic support layer. The metal nanowires include at least one of silver nanowires, gold nanowires, or copper nanowires; the porous elastic support layer is made of an elastomeric polymer, specifically including at least one of thermoplastic polyurethane, styrene-ethylene / butene-styrene block copolymer, polyether block amide, polyvinyl butyral, or hydrogenated styrene-butadiene-styrene block copolymer. The method for preparing the slit-porous epidermal electrode based on metal nanowires includes the following steps: S1: The surface of the metal nanowires was modified using a hydrophobic modifier, and after purification, the nanowires were dispersed in a polar solvent to obtain a modified nanowire dispersion. S2: The dispersion is added to the water surface, and the nanowires are made to form a densely packed conductive layer with slits at the gas-liquid interface through an interface-driven method, and then transferred to a rigid substrate. S3: A porous elastic support layer is directly constructed on the conductive layer using the static breathing diagram method or the phase separation method. S4: The electrode is obtained after curing.
7. A slit-porous epidermal electrode based on metal nanowires according to claim 6, characterized in that, The hydrophobic modifier is selected from one or more of n-octadecyl mercaptan, n-hexadecyl mercaptan, or n-dodecyl mercaptan.
8. A slit-porous epidermal electrode based on metal nanowires according to claim 6, characterized in that, The outer surface of the porous elastic support layer is treated with plasma hydrophilicity, or coated with a hydrophilic polymer on one side, or deposited with an ultrathin hydrophilic film on one side by vapor deposition.
9. A slit-porous epidermal electrode based on metal nanowires according to claim 6, characterized in that, The interface-driven methods include interface-driven flow induced by a movable baffle compression method or surfactant-induced interface flow.
10. A slit-porous epidermal electrode based on metal nanowires according to claim 6, characterized in that, The static breathing diagram method in step S3 is as follows: the elastomer polymer is dissolved in an organic solvent to prepare a polymer solution, which is then dropped onto a substrate carrying a nanowire conductive layer and leveled. The solution is then transferred to a constant temperature and humidity environment, and water vapor is introduced to regulate the relative humidity of the environment. The template effect of the water droplets is used to induce the formation of a porous elastic support layer. After curing, a slit porous skin electrode is obtained.
Citation Information
Patent Citations
Gas permeable, ultrathin, stretchable epidermal electronic devices and related methods
US20220340726A1